Prevalence of Hypomineralized Second Primary Molar in Shaanxi, China - Abdalla, Lamya Khalafalla Altieab; Zhu, Shijie; Zhang, Pingneng; Huang, Peidi; Guo, Kaixin; Zhang, Wenjiao; Zhang, Bin; Hu, Xiao; Huang, Ruizhe (Frontiers in Public Health, 2025)
ObjectivesThis cross-sectional study aimed to determine the prevalence of Hypomineralized Second Primary Molar (HSPM) in 3–5-year-old children in Shaanxi Province, China, and identify its associated factors, with a specific focus on exploring the potential role of pregnancy vomiting that have been less studied previously.MethodsSubjects were randomly sampled from three cities in Shaanxi Province, namely Xi’an, Yan’an, and Weinan. HSPM was evaluated through oral examinations, while other health-related data were gathered using questionnaires. Statistical analyses were performed using chi-square tests and binary logistic regression to identify independent risk factors and adjust for confounders.ResultsA total of 1,022 questionnaires were distributed, with 1,015 valid ones collected from children in three cities. The sample included 48.97% males and 51.03% females, with regional distributions of 45.71% (Xi’an), 27.78% (Weinan), and 26.51% (Yan’an) of the sample. The overall prevalence of HSPM was 7.09%, showing differences by region and maternal education. Teeth with HSPM had a higher caries rate (55.6%) than those without (45.3%), though the difference was not significant. Univariate analysis linked HSPM to gestational age (p = 0.022), asthma in the first year of life (p = 0.03), measles (p = 0.003) and maternal nausea (p = 0.018), in the adjusted multivariable model, maternal education (bachelor’s degree, OR = 0.297, 95%CI: 0.122, 0.72) and maternal vomiting (OR = 1.694, 95%CI: 1.027, 2.795) associated with HSPM.ConclusionThe prevalence of HSPM in Shaanxi is within the global range, while maternal lower education level and pregnancy vomiting are key risk factors for HSPM. These findings provide novel insights for targeted prenatal interventions to prevent HSPM in preschool children.